THE IMPACT OF GENDER ON LANGUAGE LEARNING MOTIVATION AND ATTITUDES - Aswad, Muhammad (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
This research highlights the importance of understanding how gender affects students' motivation and attitudes in learning English, especially in an era of globalization that increasingly demands foreign language skills. In this context, the research method used is a literature study, in which various sources and previous research are analyzed to understand related trends and patterns. The results show that there are significant differences between male and female students in terms of motivation and attitude towards learning English. In particular, female students show higher integrative motivation, which means they are more driven to learn English as part of their personal identity and to interact with communities that use the language. In addition, their positive attitude towards learning English was more prominent compared to male students. These findings point to the importance of designing teaching strategies that are sensitive to gender differences, with the aim of creating an inclusive and supportive learning environment for all students, regardless of their gender. These strategies could include more personalized and adaptive approaches, which take into account the needs and motivations of individual students, so that the learning process becomes more effective and equitable.